The globalization of missed nursing care terminology - Willis, Eileen; Zeleníková, Renáta; Bail, Kasia; Papastavrou, Evridiki (My University, 2021)
Aim: To determine if there are cross-national differences in nurse understandings of the terms: missed care, rationed care and care left undone. Background: Nurse researchers from a number of countries have published studies on missed and rationed care. It is not clear if there are differences in understanding the key terms across various language groups. Design: A mixed method questionnaire was distributed to 26 member countries of a nursing research consortium in 2017. Methods: Forty-five responses to a qualitative questionnaire were received; 80% were nurse researchers. These responses were categorized into language groups and analysed for congruence and differences. Findings: There was congruence across all language groups in interpreting the three terms. Giddens' theory of globalization provides an explanation for this congruence. Conclusion: Shared understandings are explained by the fact that the majority of participants are nurse researchers with knowledge of English and the research literature. Shared understanding within the globalized academic community does not necessarily translate for clinical or nurse managers, nor does it predetermine solutions.
Keywords: Globalization; Missed care; Nurse; Patient safety; Rationed care